An annotated and illustrated list of Cephalopoda (Mollusca) recorded from Brazilian waters, with an identification key to species - Manuel Haimovici; Roberta Aguilar dos Santos; Luciano Gomes Fischer; Mario A. Salcedo Vargas; Tatiana Silva Leite (Marine and Fishery Sciences)
An annotated list of cephalopods from the Brazilian Economic Exclusive Zone is presented. Species are briefly described, mainly based on external characters with information on their habitat and distribution, and images of freshly caught or preserved specimens are given. This list updates the nomenclature and geographical distribution given in previous lists, and it includes some recently described species, as well as unpublished records identified to genera. A key for the identification of families, genera and species, and images of live specimens are included. A total of 93 species are recorded, belonging to the orders Spirulida (1), Sepioidea (6), Myopsida (6), Oegopsida (46), Bathyteuhida (2), Vampyromorpha (1) and Octopoda, suborders Cirrata (4) and Incirrata (27), all in the Subclass Coloidea. Almost half of the species are benthic from the continental shelf or slope, and the remainder are water-column species, mostly from the slope and adjacent oceanic waters. Only 17 species are considered endemic to the southwest Atlantic, including two that are currently known to occur only in Brazil.